Modulation of the formation of active forms of nitrogen by ingredients of plant products in the inhibition of carcinogenesis - V. P. Deryagina; V. P. Reutov (Успехи молекулярной онкологии)
The review analyzes literature data and the results of our own research on the role of reactive nitrogen species (NO, NO2, N2O3) in the initiation and progression of tumors. The possibility of modulating the activity of inducible NO synthase by the biologically active components of plant products and their effect on carcinogenesis is analyzed. Possible mechanisms of the ambiguous action of NO and its metabolic products in the mechanisms of carcinogenesis are discussed. The generalization and analysis of these data allowed us to formulate some principles for the use of substances that modulate the activity of inducible NO synthase and affect the formation of NO and its metabolic products in inhibiting carcinogenesis.